Performance Analysis of a Producer Gas-fuelled Heavy-duty SI Engine at Full-load Operation. (December 2015) - Gobbato, Paolo; Masi, Massimo; Benetti, Marianna
Abstract: Biomass gasification converts a solid fuel into a gaseous mixture (syngas or producer gas) which can be burnt in reciprocating internal combustion engines (ICEs) to produce electrical power. A wide variety of bio-residues can be processed to obtain syngas, making biomass gasification a very interesting way to exploit the energy content of industrial by-products and agricultural wastes. This paper focuses on the operation of a spark ignition (SI) ICE burning low-heating value gas produced in a fixed-bed downdraft gasifier. The biomass gasification power plant has collected more than nine months of operation till now without need of any extraordinary maintenance of the engine. Engine performance is calculated using experimental data acquired at different air-to-fuel ratios and spark timings, and then compared with results of test performed by other authors. The work is mainly aimed at analysing the effect of PG fuelling on brake power, efficiency and emissions of heavy-duty engines.